Reduction of CT artifacts from cardiac implantable electronic devices using a combination of virtual monoenergetic images and post-processing algorithms - Pennig, Lenhard; Zopfs, David; Gertz, Roman; Bremm, Johannes; Zaeske, Charlotte; Große Hokamp, Nils; Celik, Erkan; Goertz, Lukas; Langenbach, Marcel; Persigehl, Thorsten; Gupta, Amit; Borggrefe, Jan; et al. (European radiology, 2021)
Objectives To evaluate the reduction of artifacts from cardiac implantable electronic devices (CIEDs) by virtual monoenergetic images (VMI), metal artifact reduction (MAR) algorithms, and their combination (VMI MAR ) derived from spectral detector CT (SDCT) of the chest compared to conventional CT images (CI). Methods In this retrospective study, we included 34 patients (mean age 74.6 ± 8.6 years), who underwent a SDCT of the chest and had a CIED in place. CI, MAR, VMI, and VMI MAR (10 keV increment, range: 100–200 keV) were reconstructed. Mean and standard deviation of attenuation (HU) among hypo- and hyperdense artifacts adjacent to CIED generator and leads were determined using ROIs. Two radiologists qualitatively evaluated artifact reduction and diagnostic assessment of adjacent tissue. Results Compared to CI, MAR and VMI MAR ≥ 100 keV significantly increased attenuation in hypodense and significantly decreased attenuation in hyperdense artifacts at CIED generator and leads ( p < 0.05). VMI ≥ 100 keV alone only significantly decreased hyperdense artifacts at the generator ( p < 0.05). Qualitatively, VMI ≥ 100 keV, MAR, and VMI MAR ≥ 100 keV provided significant reduction of hyper- and hypodense artifacts resulting from the generator and improved diagnostic assessment of surrounding structures ( p < 0.05). Diagnostic assessment of structures adjoining to the leads was only improved by MAR and VMI MAR 100 keV ( p < 0.05), whereas keV values ≥ 140 with and without MAR significantly worsened diagnostic assessment ( p < 0.05). Conclusions The combination of VMI and MAR as well as MAR as a standalone approach provides effective reduction of artifacts from CIEDs. Still, higher keV values should be applied with caution due to a loss of soft tissue and vessel contrast along the leads. Key Points • The combination of VMI and MAR as well as MAR as a standalone approach enables effective reduction of artifacts from CIEDs. • Higher keV values of both VMI and VMI MAR at CIED leads should be applied with caution since diagnostic assessment can be hampered by a loss of soft tissue and vessel contrast. • Recommended keV values for CIED generators are between 140 and 200 keV and for leads around 100 keV.